Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Hasil Audit Di Lingkungan Pemerintah Daerah Kabupaten Berau - Siti Munawaroh (Jurnal Ekonomi STIEP, 2019)
The purpose of this research is to know the effects of the competence to audit quality withindependence and capability as intervening variables at Inspektorat Berau Regency. The population are theemployees of Inspektorat Berau Regency, and samples were taken as many as 30 employees by purposivesampling method. The criteria of sample was the auditor have responsibilities in the auditing. Data wereanalyzed using Partial Least Squares-Structural Equation Model (SEM) through SmartPLS Ver. 3.2.7.The results showed that competence directly positive and significant effect on independence,capability, and audit quality. independence has a positive and significant effect on capability, and auditquality. capability has a positive and significant effects on audit quality.